Pengaruh Kecerdasan Emosional Dan Kecerdasan Adversity Terhadap Tingkat Pemahaman Akuntansi Pada Mahasiswa Pendidikan Akuntansi Dengan Minat Belajar Sebagai Variabel Intervening - Rahel May Carry Sibuea; Choms Gary Ganda Tua Sibarani; Andri Zainal (Universitas Negeri Medan (UNIMED), 2024)
This study aims to determine; (1) the effect of emotional intelligence on the level of basic accounting understanding of students of the 2021 accounting education study program at Medan State University; (2) the effect of adversity intelligence on the level of basic accounting understanding of students of the accounting education study program class of 2021 at Medan State University; (3) the influence of emotional intelligence on the learning interest of students of the accounting education study program class of 2021 at the Medan State University; (4) the influence of adversity intelligence on the learning interest of students of accounting education study program class of 2021 Medan State University (5) the effect of learning interest on the level of basic accounting understanding of students of accounting education study program class of 2021 Medan State University; (6) the effect of emotional intelligence on the level of basic accounting understanding through interest in learning; (7) the effect of adversity intelligence on the level of understanding of basic accounting through interest in learning. The population in this study were 64 students with the sampling technique using total sampling. Retrieval of data using a questionnaire of 13 statements and a test of 20 questions. The data were processed using path analysis and the Sobel test with the help of SPSS 26. The results of this study indicate that (1) emotional intelligence has a positive and significant effect on the level of students' understanding of accounting as evidenced by the coefficient value of 2.696 and tcount > ttable 7.303>1.999 with a significance of 0.000; (2) Adversity intelligence has a positive and significant effect on the level of students' understanding of accounting as evidenced by the coefficient value of 2.523 and tcount > ttable 6.385> 1.999 with a significance of 0.000; (3) Emotional intelligence has a positive and significant effect on student learning interest as evidenced by the coefficient value of 0.436 and tcount > ttable 4.742>1.999 with a significance of 0.000; (4) Adversity intelligence has a positive and significant effect on student learning interest as evidenced by the coefficient value of 0.521 and tcount > ttable 6.069> 1.999 with a significance of 0.000; (5) interest in learning has a positive and significant effect on the level of students' understanding of accounting as evidenced by the coefficient value of 3.194 and tcount > ttable 7.313>1.999 with a significance of 0.000; (6) Emotional intelligence through interest in learning has a positive and significant effect on the level of understanding of student accounting as evidenced by the coefficient value of 0.781 and tcount > ttable 3.4666> 1.999 with a significance of 0.000; (7) Emotional intelligence through interest in learning has a positive and significant effect on the level of understanding of student accounting as evidenced by the coefficient value of 0.732 and tcount > ttable 3.4666 with a significance of 0.000.Keywords : Emotional Intelligence, Adversity Intelligence, Level of Understanding of Accounting, Interest in Learning